Evaluation in situ of tag formation in dental enamel submitted to microabrasion technique: effect of two etching times - Hoeppner, Márcio Gramma; Mauro, Silvio José [UNESP]; Alexandre, Rodrigo Sversut [UNESP]; Sundefeld, Maria Lucia Marçal Mazza [UNESP]; Sundfeld, Renato Herman [UNESP] (Sociedad Argentina de Investigación Odontológica, 2010)
The objective of this study was to analyze the formation of resin tags on enamel surfaces submitted or not to enamel microabrasion technique. Thirteen undergraduate dental students received removable acrylic palatal appliances on which four sections from intact premolars were fixed, measuring 4.0 mm X 4.0 mm. Two sections received the application of a microabrasive system and the remaining sections did not receive any surface treatment. The patients were instructed to wear the acrylic palatal appliances for 4 months during the day. After this time, the sections were etched with 37% phosphoric acid for 15 seconds (sections 1 and 2) and 60 seconds (sections 3 and 4), followed by adhesive system and composite resin applications. All the sections were prepared for light microscopy analysis to observe the degree of resin penetration (x400). The results were submitted to a three-way analysis of variance with a significance level of 5%. The difference between groups was verified by the Tukey test, at a significance level of 5%. The results showed that microabraded enamel required a longer period of acid etching for longer resin tags.

O objetivo deste estudo foi analisar a formação de tags resinosos em esmalte dental submetido ou não à técnica de microabrasão. Treze estudantes de Odontologia receberam a aplicação de um aparelho ortodôntico removível contendo quatro secções de esmalte com dimensões de 4.0 mm X 4.0 mm. Duas seções receberam a aplicação de um composto microabrasivo e as demais não receberam nenhum tratamento. Os pacientes foram instruídos a usar os aparelhos ortodônticos durante o dia e por quatro meses. Após este período, as secções foram condicionadas com ácido fosfórico 37% por 15 segundos (seções 1 e 2) e por 60 segundos (secções 3 e 4), seguido pela aplicação do sistema adesivo e de resina composta. Todas as secções foram preparadas para análise em microscopia óptica comum para observar o grau de penetração do material resinoso (x400). Os resultados foram submetidos à análise de variância a três critérios, ao nível de 5%. A diferença entre os grupos foi verificada pelo teste de Tukey, ao nível de 5%. Os resultados mostraram que maiores tempos de condicionamento ácido do esmalte dental são exigidos para uma maior penetra- ção do sistema adesivo.
Avaliação in situ da formação dos tags no esmalte dental submetido à técnica da microabrasão: efeito de dois tempos de condicionamento
Keywords: Microscopy; Enamel microabrasion; Dental etching; Microscopia; Microabrasão do esmalte; Condicionamento ácido